The multifunctional roles of autophagy in the innate immune response: Implications for regulation of transplantation rejection - Zhang, Kunli; Huang, Qiuyan; Peng, Laru; Lin, Sen; Liu, Jie; Zhang, Jianfeng; Li, Chunling; Zhai, Shaolun; Xu, Zhihong; Wang, Sutian (Frontiers in Cell and Developmental Biology, 2022)
Organ transplantation is the main treatment for end-stage organ failure, which has rescued tens of thousands of lives. Immune rejection is the main factor affecting the survival of transplanted organs. How suppress immune rejection is an important goal of transplantation research. A graft first triggers innate immune responses, leading to graft inflammation, tissue injury and cell death, followed by adaptive immune activation. At present, the importance of innate immunity in graft rejection is poorly understood. Autophagy, an evolutionarily conserved intracellular degradation system, is proved to be involved in regulating innate immune response following graft transplants. Moreover, there is evidence indicating that autophagy can regulate graft dysfunction. Although the specific mechanism by which autophagy affects graft rejection remains unclear, autophagy is involved in innate immune signal transduction, inflammatory response, and various forms of cell death after organ transplantation. This review summarises how autophagy regulates these processes and proposes potential targets for alleviating immune rejection.